PENGARUH KEMAMPUAN BEBAN PAJAK TANGGUHAN, PROFITABILITAS, AKRUAL DAN PERENCANAAN PAJAK DALAM MEMPREDIKSI MANAJEMEN LABA DENGAN ASSET PAJAK TANGGUHAN SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia pada Periode 2013-2016) - Siti Raihani; Emrinaldi Nur Emrinaldi Nur; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of the ability of deferred tax burden, profitability, accruals and tax planning in predicting earnings management with deferred tax assets as intervening variables in manufacturing companies food and beverage sub-sector listed on the Stock Exchange Year 2013-2016.The population used is manufacturing companies food and beverage sub-sector listed on Indonesia Stock Exchange (BEI) in 2013 until 2016 which amounted to 16 companies. the method used is purposive sampling (purposed sample). In accordance with the results of sample selection above, then obtained the number of research samples as many as 13 companies. so the total sample size is 52 data. Model analysis of hypothesis test data in this research is path analysis analysis model.The results of the research show that: 1) deferred tax burden has no significant effect on earnings management, 2) profitability has a significant effect on earnings management. 3) Deferred tax assets have a significant influence on earnings management, 4) accruals have a significant influence on earnings management 5) tax planning does not significantly affect earnings management, 6) Indirectly profitability significantly affects earnings management through deferred tax assets. The indirect effect of profitability on earnings management through deferred tax assets is 2.28%.Keywords :Deferred Tax Expense, Profitability, Accruals, Tax Planning Of Deferred Tax Assets, Earnings Management